2014
DOI: 10.1016/j.qref.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Implications of limited investor attention to customer–supplier information transfers

Abstract: We examine the (dis)incentive effects created by the respective tax systems to invest in human capital in Atlantic Canada and compare this to a select group of provinces from the rest of Canada. While findings show a steady decline in effective tax rates through the years, thereby creating an incentive effect to invest in post-secondary education, disproportionately higher rate gap differentials in the Atlantic Provinces, on average, combined with negative comparative statics reveal a somewhat different undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 311 publications
(483 reference statements)
0
1
0
Order By: Relevance
“…Dependent suppliers and their large customers are presumed to be able to keep financial and operations information private until the formal earnings announcement to the general capital market, but not from sophisticated short sellers . Without short sellers, herd‐like behavior coupled with diversified investment strategies may prevent investigation of firm‐specific linked supply chain‐specific factors that lead to information asymmetry about future earnings (Zhu, ). H3 : The likelihood of a negative earnings surprise is preceded by high short interest for suppliers and customers, but more so for linked partners . …”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Dependent suppliers and their large customers are presumed to be able to keep financial and operations information private until the formal earnings announcement to the general capital market, but not from sophisticated short sellers . Without short sellers, herd‐like behavior coupled with diversified investment strategies may prevent investigation of firm‐specific linked supply chain‐specific factors that lead to information asymmetry about future earnings (Zhu, ). H3 : The likelihood of a negative earnings surprise is preceded by high short interest for suppliers and customers, but more so for linked partners . …”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Information externalities occur when one company's disclosed information becomes relevant to the stakeholders of another company (e.g., Badertscher et al, 2013). Previous research has demonstrated the presence of externalities with earnings information between customer firms and their suppliers (e.g., Cho et al, 2020;Pandit et al, 2011;Zhu, 2014;Chen et al, 2021). However, whether sales information has similar externalities along the supply chain remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%